Soap is not enough: handwashing practices and knowledge in refugee camps, Maban County, South Sudan. Issue 1 (December 2015) - Phillips, Raina; Vujcic, Jelena; Boscoe, Andrew; Handzel, Thomas; Aninyasi, Mark; Cookson, Susan; Blanton, Curtis; Blum, Lauren; Ram, Pavani
Abstract Background Refugees are at high risk for communicable diseases due to overcrowding and poor water, sanitation, and hygiene conditions. Handwashing with soap removes pathogens from hands and reduces disease risk. A hepatitis E outbreak in the refugee camps of Maban County, South Sudan in 2012 prompted increased hygiene promotion and improved provision of soap, handwashing stations, and latrines. We conducted a study 1 year after the outbreak to assess the knowledge, attitudes, and practices of the refugees in Maban County. Methods We conducted a cross sectional survey of female heads of households in three refugee camps in Maban County. We performed structured observations on a subset of households to directly observe their handwashing practices at times of possible pathogen transmission. Results Of the 600 households interviewed, nearly all had soap available and 91 % reported water was available "always" or "sometimes". Exposure to handwashing promotion was reported by 85 % of the respondents. Rinsing hands with water alone was more commonly observed than handwashing with soap at critical handwashing times including "before eating" (80 % rinsing vs. 7 % washing with soap) and "before preparing/cooking food" (72.3 % vs 23 %). After toilet use, 46 % were observed to wash hands with soap and an additional 38 % rinsed with water alone. Conclusions Despite intensive messaging regarding handwashing with soap and access to soap and water, rinsing hands with water alone rather than washing hands with soap remains more common among the refugees in Maban County. This practice puts them at continued risk for communicable disease transmission. Qualitative research into local beliefs and more effective messaging may help future programs tailor handwashing interventions.